The PANDA Detector at FAIR - Schmidt, M. (Ukrainian Journal of Physics, 2019)
PANDA is a fixed-target experiment that is going to address a wide range of open questions in the hadron physics sector by studying the interactions between antiprotons with high momenta and a stationary proton target. The PANDA detector is currently under construction and will be situated in the HESR that is a part of the future FAIR accelerator complex on the area of the GSI Helmholtzzentrum f¨ur Schwerionenforschung in Darmstadt. The key features of the detector are: the precise tracking in strong magnetic fields, excellent particle identification, and high-resolution calorimeters.